Nanostructure analysis of particulate matter emitted from a diesel engine equipped with a NTP reactor. (15th March 2017) - Gao, Jianbing; Ma, Chaochen; Xing, Shikai; Sun, Liwei; Huang, Liyong
Highlights: Partial oxidation happened for PM after exhaust flowed through plasma zone. PM nanostructures were with hollow cores after heat-treatment. Activation energy and rate constant were closely related to nanostructure parameters. Abstract: An investigation of the nanostructures of particulate matter (PM) emitted from a diesel engine equipped with a non-thermal plasma (NTP) after-treatment device was conducted. Raw PM, PM escaping from the NTP reactor (PM-NTP), and PM collected on the collection plate (PM aggregation) were sampled at different engine loads. High-resolution transmission electron microscopy (HRTEM) images were used to analyse the nanostructures. Raw PM showed onion like structures with short lattice fringes, however, core-shell like structures were observed for PM sampled at 60% engine load after exhaust flowed through the NTP reactor. The diameter decreased for PM-NTP and PM aggregation compared with raw PM, regardless of the engine loads. The core-shell like structures were evident after PM was partially oxidized. The average fringe separation distance, length, and tortuosity were 0.95–1.26 nm, 2.90–3.70 nm, and 1.45–1.97 respectively. The fringe separation distance increased with increasing engine load for the same kind of PM. The influence of plasma on the changes of nanostructure parameters was greatly dependent on the engine loads. The fringe length dominated the changes of the instantaneous activation energy during the oxidation process, while it was less important for apparent rate constant.